A retinaculum-sparing surgical approach preserves porcine stifle joint cartilage in an experimental animal model of cartilage repair - Marcelo B. Bonadio (Journal of Experimental Orthopaedics, 2017)
Abstract Background This study compares a traditional parapatellar retinaculum-sacrificing arthrotomy to a retinaculum-sparing arthrotomy in a porcine stifle joint as a cartilage repair model. Findings Surgical exposure of the femoral trochlea of ten Yucatan pigs stifle joint was performed using either a traditional medial parapatellar approach with retinaculum incision and luxation of the patella (n = 5) or a minimally invasive (MIS) approach which spared the patellar retinaculum (n = 5). Both classical and MIS approaches provided adequate access to the trochlea, enabling the creation of cartilage defects without difficulties. Four full thickness, 4 mm circular full-thickness cartilage defects were created in each trochlea. There were no intraoperative complications observed in either surgical approach. All pigs were allowed full weight-bearing and full range of motion immediately postoperatively and were euthanized between 2 and 3 weeks. The traditional approach was associated with increased cartilage wear compared to the MIS approach. Two blinded raters performed gross evaluation of the trochlea cartilage surrounding the defects according to the modified ICRS cartilage injury classification. The traditional approach cartilage received a significantly worse score than the MIS approach group from both scorers (3.2 vs 0.8, p = 0.01 and 2.8 vs 0, p = 0.005 respectively). Conclusion The MIS approach results in less damage to the trochlear cartilage and faster return to load bearing activities. As an arthrotomy approach in the porcine model, MIS is superior to the traditional approach.